PENGARUH PEMBERIAN TEH HIJAU TERHADAP PENURUNAN KADAR KOLESTEROL PADA LANSIA DI KECAMATAN BATANG TORU KABUPATEN TAPANULI SELATAN - VIKTOR EDYWARD MARBUN; JOHANNES SEMBIRING; ANGGUN SYAFITRI (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2023)
Cholesterol is a fat found in the bloodstream or body cells, is necessary for the formation of cell walls, and is necessary as a raw material for several hormones. High levels of cholesterol cause it to react with other substances and precipitate in the arteries which will eventually cause atherosclerosis so that it disrupts the process of blood circulation to the heart. Many factors cause hypercholesterolemia, namely genetic factors, obesity factors, dietary factors and rarely exercise. Cholesterol can be overcome with herbs such as guava, turmeric, berimbing ur and noni. One of them is green tea. Green tea is one of the non-pharmacological treatments that can reduce cholesterol levels in the elderly in Batang Toru sub-district, South Tapanuli Regency. It was found that cholesterol levels before drinking green tea were 247 mg/Dl and after drinking green tea were 214 mg/Dl. This study aims to determine the effect of giving green tea on reducing cholesterol levels in the elderly in 2020. This study used a quasi-experimental method with a one-group pretest-posttest design. Study results conclude that green tea lowers cholesterol in older adults. It is recommended to the public to be able to make green tea as an option in dealing with increased cholesterol levels.